THE ESSENCE OF THE COEFFICIENT OF VARIATION IN THE PROBABILITY APPROACH IN CHECKING THE STRENGTH OF CONCRETE AND REINFORCED CONCRETE STRUCTURES - Saxiba Mirzababaeva (Journals Park Publishing, 2023)
The article discusses the scientific significance of the research results, scientific research and analysis of the influence of the coefficient of variation of the material on the reliability of reinforced concrete structures, the influence of the coefficient of variation of the material on the reliability of reinforced concrete structures using practical experiments, discusses the experimental results of comparing the existing structure with the normative ones and identifying inconsistencies. During the study, the scientific works of a number of scientists were studied [1-23].
Keywords: concrete and reinforced concrete, building material, destructive testing, non-destructive testing, strength class, bending strength, strength.